Cloning, expression analysis, and RNA interference study of a HORMA domain containing autophagy-related gene 13 (ATG13) from the coleopteran beetle, Tenebrio molitor - Lee, Jung Hee; Jo, Yong Hun; Patnaik, Bharat Bhusan; Park, Ki Beom; Tindwa, Hamisi; Seo, Gi Won; Chandrasekar, Raman; Lee, Yong Seok; Han, Yeon Soo (Frontiers in Physiology, 2015)
Autophagy is a process that is necessary during starvation as it replenishes metabolic precursors by eliminating damaged organelles. Autophagy is mediated by more than 35 autophagy-related (Atg) proteins that manifest in the nucleation, elongation, and curving of autophagosome membrane. We isolated a homolog of an ATG13 gene from the transcriptome database of the larva of the mealworm beetle, Tenebrio molitor (designated as TmATG13). The sequence analysis showed that TmATG13 cDNA comprises of 1,176 bp open reading frame that encodes a protein of 391 amino acids. Analyses of the structure-specific features of TmAtg13 showed an intrinsically disordered middle and C-terminal region, rich in regulatory phosphorylation sites. The N-terminal Atg13 domain show a HORMA (Hop1, Rev7, and Mad2) fold containing conserved amino acid residues across the Atg13 orthologs in insects. qRT-PCR revealed that TmATG13 was expressed ubiquitously in all the developmental stages of insect. TmATG13 mRNA expression was high in fat body and gut of the larval and adult stages of the insect. During ovary development and maturation, the TmATG13 transcripts showed high expression until six days of development, followed by a significant decline. The prospective functions mediated by TmAtg13 during autophagy will be clarified by further studies in the near future.